Assessing a Customized, Interactive Online Information Tutorial: The Getting Started with Research Module - Amsberry, Dawn; Behler, Anne (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
After creating an online information literacy tutorial in response to the shift to online learning due to the COVID-19 pandemic, a team of six library employees developed a multi-pronged approach to assessing the module to determine how well it met the stated learning objectives. This article describes the assessment of the Getting Started With Research information literacy module, a learning experience developed using Articulate Rise 360 software and accompanied by a Google Forms research log for students to complete. The authors present results from both a rubric-driven and textual analysis study undertaken to assess student responses to the research logs, and they discuss how the study’s findings will inform future practice.